Current Perspectives on “Off-The-Shelf” Allogeneic NK and CAR-NK Cell Therapies - Heipertz, Erica L.; Zynda, Evan R.; Stav-Noraas, Tor Espen; Hungler, Andrew D.; Boucher, Shayne E.; Kaur, Navjot; Vemuri, Mohan C. (Frontiers in Immunology, 2021)
Natural killer cells (NK cells) are the first line of the innate immune defense system, primarily located in peripheral circulation and lymphoid tissues. They kill virally infected and malignant cells through a balancing play of inhibitory and stimulatory receptors. In pre-clinical investigational studies, NK cells show promising anti-tumor effects and are used in adoptive transfer of activated and expanded cells, ex-vivo. NK cells express co-stimulatory molecules that are attractive targets for the immunotherapy of cancers. Recent clinical trials are investigating the use of CAR-NK for different cancers to determine the efficiency. Herein, we review NK cell therapy approaches (NK cell preparation from tissue sources, ways of expansion ex-vivo for "off-the-shelf" allogeneic cell-doses for therapies, and how different vector delivery systems are used to engineer NK cells with CARs) for cancer immunotherapy.